Experimental organic chemistry - Toh, Rong; Choo, Jiang (Arcler Press, 2015)
Organic chemistry is a chemistry sub discipline involving the scientific study of the structure, properties, and reactions of organic compounds and organic materials, i.e., matter in its various forms that contain carbon atoms. Study of structure includes using spectroscopy, mass spectroscopy, and other physical and chemical methods to determine the chemical composition and constitution of organic compounds and materials. The text provides a rigorous account of the principles and practice of experimental organic chemistry. A microscale approach has been integrated alongside conventional manipulations, bringing it in line with current laboratory practice. The book "Experimental organic Chemistry" contains six chapters. The measurements of remote water temperature based on brillouin scattering with a frequency doubled pulsed YB have been discussed in first chapter. The synthesis of diamides and diimines have been described in second chapter. Simultaneous measurements of chlorophyll concentrations by lidar have been introduced in third chapter. In fourth chapter, we report various uses of PTC in syntheses and reactions of five-membered heterocycles compounds and their multifused rings. The aim of fifth chapter is to put in perspective radical chemistry, moving it away from its origin as a synthetic means for solid supports, to becoming a useful tool for the synthesis of small molecules. A brief survey of known named organic reactions discovered by Italian chemists, along with their historical contextualization, is presented in sixth chapter.